Continuous Bilateral Erector of Spine Plane Block at T8 for Extensive Lumbar Spine Fusion Surgery: Case Report. Issue 5 (15th March 2019) - Almeida, Carlos Rodrigues; Oliveira, Ana Raquel; Cunha, Pedro
Abstract: Introduction: Supplementary strategies, in combination with conventional analgesia, for pain control after lumbar fusion surgery remain limited. Case Description: Here, we describe a 79‐year‐old woman who experienced pain (10/10 on a numeric rating scale) on postoperative day 1 after undergoing L2 to S1 spine fusion. Erector spinae plane (ESP) blocks were performed at T8 and, after a bolus of ropivacaine 0.2% (20 mL) per side, perineural catheters were placed bilaterally. Continuous infusion (5 mL/h) of ropivacaine 0.2% per side was maintained for 48 hours. During this period, 2 boluses (15 mL) per day of ropivacaine 0.2% were administered bilaterally to maintain optimal analgesia. Discussion: Bilateral ESP catheterizations at T8, placed remotely from the surgical site, may be considered for patients undergoing extensive spinal fusion procedures, because they contribute to significant analgesic improvement, without significant motor block; the effect of the block remains mostly in the posterior rami of spinal nerves and in the posterior bony elements of the vertebrae. The risk for hematoma or bacterial colonization related to catheter placement at T8 level using epidural or ESP techniques is low; nevertheless, a delay in the diagnosis of postoperative epidural hematoma or abscess directly related to the surgical intervention is a potential concern in spine fusion surgery. However, the action of an ESP block is primarily in the posterior rami of the spinal nerves, which makes an eventual neuraxial compression less likely to be masked by an ESP block compared with an epidural block, because an ESP hematoma or infection will not directly impinge on the spinal cord. Lay Summary: A 79‐year‐old woman experienced excruciating pain on post‐operative day 1 after undergoing L2 to S1 spine fusion. Bilateral continuous erector spinae plane (ESP) blocks were performed at T8 and, after a bolus of ropivacaine 0.2% (20 mL) per side, a continuous infusion (5 mL/hour) of ropivacaine 0.2% per side was maintained for 48 hours, which provided effective analgesia. During this period, two boluses (15 mL) per day of ropivacaine 0.2% were administered bilaterally to maintain optimal analgesia. ESP catheterizations at T8, placed remotely from surgical site, may be considered in extensive lumbar spinal fusion cases.